Digital Assessment Data to Provide Formative Feedback in Mathematics: A Longitudinal Study of Teachers’ Engagement with QUOP in Austria - Ackerlauer, Petra; et al. (Teacher Development, 2025)
Educational reforms have increasingly emphasized the use of formative digital assessments, with the implementation of QUOP in Upper Austria as a key example. While much of the existing research explores how such digital tools support formative feedback in classrooms with ongoing teacher support, there is limited understanding of how teachers independently engage with these tools over time. This study examines five primary school teachers in Austria who used QUOP with minimal external support over a period of four years. Our central research question was: To what extent can teachers using QUOP without training handle data for formative purposes and improve independently over time? The results showed that while teachers moved from symbolic to pragmatic and sometimes unsystematic data use, achieving a fully systematic approach required converging several critical factors. Teachers with limited experience and low perceived usefulness of digital tools struggled to move beyond basic data use, though cooperation among teachers led to more consistent formative feedback practices. Challenges included aligning long-term instructional planning with curriculum standards and addressing the diverse needs of students in large, performance-oriented classrooms. Our findings suggest that while QUOP is intuitive and can be adopted with minimal training, its sustained and effective use requires strong foundations in mathematics, data analysis, and supportive teaching environments. Thus, this study highlights the importance of fostering teachers’ mathematical knowledge and data literacy, as well as cultivating collaborative school culture
Keywords: Digital assessment; Formative feedback; QUOP; Primary School Teachers